حديث القرآن عن الجنة و آثاره الإيمانية و التربوية - سمية, ضيف; سمية, نصرات; نصيرة, ضيف (جامعة الوادي university of eloued, 2014)
لها كاف كتاب الله العزيز بالرتبة الأسهى كالهكاف الأعمى, ككاف ها اتصل ب هف الهعارؼ بالهكاف الذؼ عمهت, لذلؾ اىعقد العز عمى أف يككف عىكاف ذٌي الد ا رسة "حديث القرآف عف الجىة كآثاري الإيهاىية كالتربكية". كصف القرآف ىعي الجىة كها أعدي الله لأ مٌ اٍ هف طعا كش ا رب كلباس. كأعظ هف ذٌا كم الىظر لكج الله تعالى كرضكاى عمى أ لٌ الجىة , ج ا زءا ل ٍ لها ترككي في الدىيا طاعة لله عز كجل . ك ذٌا يدفع الهؤهف بالرغبة في تحصيل ذٌا الىعي فيجعم ا ز دٌا في الدىيا كها في اٍ هف ش كٍات ا رغبا في ثكاب الآخرة , كخالصا لله في أعهال , هستشع ا ر بالسكيىة كالطهأىيىة بطاعت لله رجاءا في رحهة الله كثكاب . كالإيهاف بىعي الجىة ل كقع في ضبط سمكؾ الهسم فيتزكد بالأعهاؿ الصالحة كيتجىب الهعاصي , ك ذٌا يجعل تصرفات ذات هسؤكلية , ك ذٌا يىعكس عمى السمكؾ بالاستقاهة كتحهم الهشاؽ كالصبر في الدىيا كايثار الآخرة عمي اٍ , بالرجاء كالخكؼ يكهل الإيهاف.The holy Quran has a great value whim consists various types of The knowledge . we have decided to chose that title of Quranic speech about paradise and its effects on faith and on educational side . Description Koran paradise and what God has prepared for her owners from food and drink, clothing and the greatest of all this is to consider the holy face of God, and His pleasure to the people of Paradise, sanction them for leaving him in the world of obedience to God Almighty. This pays the insured desire to collect this bliss ascetic in the world and where the desires of interested in the reward of the Hereafter, and God in its pure, felling tranquility and peace of mind to obey God in His mercy and hope the reward. And faith bliss the paradise signed him in fixing Muslim behavior, to became more strength to do good and avoid sin, and this makes his actions liability, reflex behavior integrity and bear hardships and patience in the world by reaching the afterlife, and hope and fear complete faith